CRM campaigns with choice for enhanced business process performance: The collectivist customers’ collaborative role for positive word-of-mouth - Christofi, Michael; Thrassou, Alkis; Chebbi, Hela; Ahmed, Zafar U.; Grandhi, Balakrishna; Iaia, Lea (My University, 2020)
Purpose: A substantial body of research evidence has now accumulated in the cause-related marketing (CRM) literature. Yet, research on positive word of mouth (WOM) in the CRM domain is scarce. Based on this, the purpose of this paper is to present a framework that enhances positive WOM persuasion in a CRM context. Design/methodology/approach: Specifically, the authors explore collectivism as a contextual dimension for positive WOM persuasion in a CRM setting and discusses three novel constructs for effectively designing such campaigns, namely, cause proximity, choice of donation type and choice variety of donation types in a single offering frame. Based on conceptual logic and drawing on literature from a variety of disciplines, this framework should provide deeper insight into achieving positive WOM persuasion with CRM strategy and implementation. Findings: Additionally, the analysis leads to specific research questions regarding the associations between these contrasts and positive WOM persuasion in a CRM context. Originality/value: Finally, the managerial and theoretical contributions are discussed, as well as directions for further research.
Keywords: Cause-related marketing; Choice; Collaborative role; Collectivism; Word of mouth